Trehalose mitigates heat stress- induced damages in wheat seedlings - Yogita, K; Madan, Shashi; Rani, Babita; Reena, K; Munjal, Renu (Journal of Cereal Research, 2025)
The present study was carried out to study the role of osmoprotective trehalose in thermotorerance of wheat (Triticum aestivum L). Ten days old seedlings of wheat cultivars WH -730 (heat tolerant) and WH- 711 (heat-sensitive) grown at 25ºC were exposed to 35ºC. These seedlings were supplied with Hogland solution containing 1mM and 2mM trehalose. All biochemical and physiological parameters were studied in control (25ºC), stressed (35ºC) and trehalose (1mM and 2mM) treated seedlings on 15th day of germination. WH-711 suffered greater damage to cellular membranes due to lipid peroxidation as indicated by higher accumulation of H2O2, MDA and enhanced activity of lipoxygenase. Activities of antioxidative enzymes, viz. ascorbate peroxidase catalase and peroxidase increased under heat stress both in tolerant and sensitive cultivars, however, activity declined with increasing concentration of trehalose.